The critical role of POCUS: Visual diagnosis of papilledema in a persistent headache patient - Tahir Shahzad (21842195) (2024)
The evaluation of headaches in emergency departments (ED) remains a formidable challenge, primarily due to the wide range of potential underlying causes. Distinguishing between benign primary headaches and secondary headaches, which may be indicative of serious pathology, is crucial for effective patient management. In this complex diagnostic landscape, the introduction of point-of-care ultrasound (POCUS) has been nothing short of revolutionary, providing rapid, real-time imaging results directly at the bedside—essential in settings where time is of the essence. Other Information Published in: Visual Journal of Emergency Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.visj.2024.102021